The Science Process Skills Of Biology Science Learning In State Junior High Schools In Percut Sei Tuan District Deliserdang Regency - Sri Susanti; Syahmi Edi; Hasruddin Hasruddin (Jurnal Pendidikan Indonesia, 2021)
This study aimed to analyze the science process skills of a scientific approach in the learning process of biology in State Junior High Schools in Percut Sei Tuan, Deli Serdang. This method applied a descriptive study with a qualitative approach. The population was all students consisting of 8 public schools in State Junior High Schools of Percut Sei Tuan for the academic year of 2020/2021. Samples were taken from 180 eighth-grade students from 5 schools in Percut Sei Tuan by using purposive sampling. To obtain the data, the description test was used as an instrument to measure students'' science process skills with indicators such as observing, classifying, interpreting, predicting, hypothesizing, planning experiments, applying concepts, and communicating in biology learning. The results on science process skills in the biology learning of plant structure and function material were categorized as good with a mean score of 72.06 and the highest indicator for observing obtained a mean score of 82.77 with a very good category and the lowest indicator for communicating obtained a mean score of 64.58 with a good category.